Peran Masyarakat Lokal dalam Pelestarian Wisata Pohon Sejuta Umat di Kecamatan Kepulauan Banda - Merti Siska Rosely; Santri A.Wagola (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aimed to explore and strengthen the role of local communities in preserving the natural tourism site known as